2008
DOI: 10.1143/jjap.47.3248
|View full text |Cite
|
Sign up to set email alerts
|

Self-Spreading Behavior of Supported Lipid Bilayer through Single Sub-100-nm Gap

Abstract: We report on the self-spreading behavior of a supported lipid bilayer passing through a sub-100-nm gap (nanogap). For this purpose, a device with a nanogap in a microchannel on a silicon substrate was designed and fabricated by electron beam lithography and photolithography. Fluorescence images of the lipid bilayer labeled with dye-conjugated lipids were observed by using a confocal laser scanning microscope. The time evolution of the self-spreading lipid bilayer passing through the nanogap was investigated at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 16 publications
6
29
0
Order By: Relevance
“…A red fluorescent single lipid bilayer developed along a microchannel from the left side. We confirmed that the lipid bilayer did not develop on the photoresist or gold pattern but only on the hydrophilic SiO 2 surface [8]. In all the present experiments, the lipid bilayer passed through a nanogap with a semicircular shape without electric field applied on the nanogap.…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…A red fluorescent single lipid bilayer developed along a microchannel from the left side. We confirmed that the lipid bilayer did not develop on the photoresist or gold pattern but only on the hydrophilic SiO 2 surface [8]. In all the present experiments, the lipid bilayer passed through a nanogap with a semicircular shape without electric field applied on the nanogap.…”
Section: Methodssupporting
confidence: 81%
“…We have demonstrated some interesting features of supported lipid bilayers that derive from the self-spreading nature of the lipid bilayer, including the observation of fluorescence resonance energy transfer [7] and the effect of a nanogap structure on the membrane [8,9]. In this study, we investigated the way that an electric field applied to a single nanogap affects the dynamics of lipid bilayers passing through the nanogap.…”
Section: Introductionmentioning
confidence: 99%
“…We have been trying to fabricate ''nano-biodevices'' by combining Si substrates possessing nanoscale features with biomolecules (i.e., lipids and ion channels). [1][2][3][4] Recently, we have demonstrated that suspended lipid bilayers (SsLBs) can be successfully and stably formed over micro-wells with an optimal substrate architecture. 5) As the next step, we examined the regulation of the ion channel protein orientation in lipid bilayers.…”
mentioning
confidence: 99%
“…This highly integrative SLB microarray fabrication technique is advantageous for use with high-throughput device architecture. Because SLB is known to self-spread through a sub-100-nm gap, 27 we can extend our technique to submicrometer arrays by using an electron beam lithography pattern that has the potential to increase the integration density by 10 2 compared with previously reported methods. We think that the composition submicroarrays can provide opportunities for previously impractical experiments.…”
Section: ' Conclusionmentioning
confidence: 99%